Brain repair and reprogramming: the route to clinical translation. (September 2016) - Grealish, S.; Drouin‐Ouellet, J.; Parmar, M.
Abstract: The adult brain has a very limited capacity for generation of new neurons, and neurogenesis only takes place in restricted regions. Some evidence for neurogenesis after injury has been reported, but few, if any, neurons are replaced after brain injury or degeneration, and the permanent loss of neurons leads to long‐term disability and loss of brain function. For decades, researchers have been developing cell transplantation using exogenous cell sources for brain repair, and this method has now been shown to successfully restore lost function in experimental and clinical trials. Here, we review the development of cell‐replacement strategies for brain repair in Parkinson's disease using the example of human foetal brain cells being successfully translated from preclinical findings to clinical trials. These trials demonstrate that cell‐replacement therapy is a viable option for patients with Parkinson's disease, but more importantly also show how the limited availability of foetal cells calls for development of novel cell sources and methods for generating new neurons for brain repair. We focus on new stem cell sources that are on the threshold of clinical application for brain repair and discuss emerging cellular reprogramming technologies. Reviewing the current status of direct neural conversion, both in vitro and in vivo, where somatic cells are directly reprogrammed into functional neurons without passing through a stem cell intermediate, we conclude that both methods result in the successful replacement of new neurons that mature and integrate into the host brain. Thus, this new field shows great promise for future brain repair, although much work is still needed in preclinical animal models before it can be seriously considered for clinical applications. Abstract : Content List – Read more articles from the symposium: Human models and technology for regenerative medicine.